R. Cremades (Coord.), D. García Gil, MªB. Lizaso Azcune, A. Morales Fernández, MªJ. Del Olmo Barros, M. Román Álvarez e I. Sustaeta Llombart (2017). Didáctica de la Música en Educación Infantil. Madrid: Ediciones Paraninfo. - Maria del Mar Bernabé Villodré, Dra (Ediciones Complutense, 2020)
Reseña del libro de R. Cremades (Coord.), D. García Gil, MªB. Lizaso Azcune, A. Morales Fernández, MªJ. Del Olmo Barros, M. Román Álvarez e I. Sustaeta Llombart (2017). Didáctica de la Música en Educación Infantil. Madrid: Ediciones Paraninfo.